2015
DOI: 10.1161/jaha.114.001508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extended‐Release Niacin on High‐Density Lipoprotein (HDL) Functionality, Lipoprotein Metabolism, and Mediators of Vascular Inflammation in Statin‐Treated Patients

Abstract: BackgroundThe aim of this study was to explore the influence of extended-release niacin/laropiprant (ERN/LRP) versus placebo on high-density lipoprotein (HDL) antioxidant function, cholesterol efflux, apolipoprotein B100 (apoB)-containing lipoproteins, and mediators of vascular inflammation associated with 15% increase in high-density lipoprotein cholesterol (HDL-C). Study patients had persistent dyslipidemia despite receiving high-dose statin treatment.Methods and ResultsIn a randomized double-blind, placebo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 58 publications
1
19
0
1
Order By: Relevance
“…164 Moreover, extended-release niacin when added to statin monotherapy resulted in lowering of lipoprotein(a) and oxidized LDL as well as the inflammatory markers SAA and monocyte chemoattractant protein-1. 165 As a consequence, like statins, also niacin has attracted research interest as a therapeutic candidate for modifying HDL structure and function. In fact, mass spectrometry-based proteome analysis revealed that 1 year combination treatment with atorvastatin (10 to 20 mg daily) plus extended-release niacin (2 g daily) in CAD patients remodeled the protein composition of HDL3 particles toward that of healthy control subjects.…”
Section: Niacinmentioning
confidence: 99%
See 1 more Smart Citation
“…164 Moreover, extended-release niacin when added to statin monotherapy resulted in lowering of lipoprotein(a) and oxidized LDL as well as the inflammatory markers SAA and monocyte chemoattractant protein-1. 165 As a consequence, like statins, also niacin has attracted research interest as a therapeutic candidate for modifying HDL structure and function. In fact, mass spectrometry-based proteome analysis revealed that 1 year combination treatment with atorvastatin (10 to 20 mg daily) plus extended-release niacin (2 g daily) in CAD patients remodeled the protein composition of HDL3 particles toward that of healthy control subjects.…”
Section: Niacinmentioning
confidence: 99%
“…No differences were observed in the protective effects of HDL against LDL oxidation between dyslipidemic patients treated with extended-release niacin/laropiprant on top of statin therapy and those treated with statin monotherapy. 165 An intervention study in patients with dyslipidemia found no significant change in serum cholesterol efflux capacity after 6 weeks of extended-release niacin therapy (titrated up to 1 g/day). 170 Similarly, adding niacin (2 g daily) to simvastatin therapy provided no additional benefit with regard to cholesterol efflux capacity and HDL inflammatory index in patients with carotid atherosclerosis, despite increasing HDL-cholesterol by 29%.…”
Section: Niacinmentioning
confidence: 99%
“…3 also includes a comparison to the HDL Cholesterol increase found in a clinical trial with Extended Release Niacin (ERN in Fig. 3), which raised HDL Cholesterol 18% (p < 0.001) in this trial [71].…”
Section: Sc100+ Increases Hdl Cholesterolmentioning
confidence: 98%
“…Total Cholesterol (TC) and blood glycosylated hemoglobin (HbA1c) levels were also tested in the [70], and Extended Release Niacin (ERN at 1500 mg/day for 6 weeks, N = 27), which is taken from a placebo-ERN crossover clinical trial [71]. All stared results are significant with p < 0.05 subjects at baseline and after 15 weeks of SC100+.…”
Section: No Significant Change In Total Cholesterol or Blood Hba1c Lementioning
confidence: 99%
“…Por lo tanto, el desarrollo farmacológico centrado en las lipoproteínas HDL no debiera enfocarse exclusivamente en la búsqueda de nuevas drogas que aumenten los niveles de colesterol HDL, sino que, además, mejoren las capacidades funcionales de las partículas de HDL. Por ejemplo, el ácido nicotínico no sólo incrementa las cifras de colesterol HDL, sino que también mejora la acción de las partículas de HDL como aceptoras de colesterol durante el eflujo celular de este lípido 11,12 . Por otro lado, nuevos fármacos en desarrollo -como los inhibidores de la proteína de transferencia de ésteres de colesterol (CETP) que elevan los niveles de colesterol HDL-también aumentan la capacidad funcional intrínseca de las partículas de HDL en el proceso de eflujo celular de colesterol 13,14 , aunque todavía no se ha demostrado su real beneficio clínico en la reducción de eventos cardiovasculares.…”
Section: Introductionunclassified